2022
DOI: 10.3390/ijms23095111
|View full text |Cite
|
Sign up to set email alerts
|

Proline Oxidation Supports Mitochondrial ATP Production When Complex I Is Inhibited

Abstract: The oxidation of proline to pyrroline-5-carboxylate (P5C) leads to the transfer of electrons to ubiquinone in mitochondria that express proline dehydrogenase (ProDH). This electron transfer supports Complexes CIII and CIV, thus generating the protonmotive force. Further catabolism of P5C forms glutamate, which fuels the citric acid cycle that yields the reducing equivalents that sustain oxidative phosphorylation. However, P5C and glutamate catabolism depend on CI activity due to NAD+ requirements. Next, Gen-O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The purified mitochondrial solution containing 300 μg protein was added to the chamber for detection. Oxygen concentration (μM) and oxygen flux (pmol‐s‐mg‐1; negative time derivative of oxygen concentration divided by mitochondrial mass per volume and corrected for instrumental background oxygen flux resulting from oxygen consumption of the oxygen sensor and back‐diffusion into the chamber) were recorded using DatLab 5.0 software (Oroboros Instruments, Austria) 18 . The RCR was expressed as state3/state4 respiratory rate.…”
Section: Methodsmentioning
confidence: 99%
“…The purified mitochondrial solution containing 300 μg protein was added to the chamber for detection. Oxygen concentration (μM) and oxygen flux (pmol‐s‐mg‐1; negative time derivative of oxygen concentration divided by mitochondrial mass per volume and corrected for instrumental background oxygen flux resulting from oxygen consumption of the oxygen sensor and back‐diffusion into the chamber) were recorded using DatLab 5.0 software (Oroboros Instruments, Austria) 18 . The RCR was expressed as state3/state4 respiratory rate.…”
Section: Methodsmentioning
confidence: 99%
“…The PYCR1 and ALDH18A1 genes, which regulate proline synthesis, are frequently highly expressed in tumour cells and contribute to proliferation and invasion [14]. Retrospective analysis has shown that proline metabolism is associated with the progression of breast, kidney cancer, colorectal, and liver cancer, as well as melanoma [15][16][17]. Elia et al [18] reported that proline metabolism increased cancer stemness and supported metastasis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are most widely studied for the capacity to produce the biological energy currency of ATP, through the coupling of oxidative phosphorylation with the electron transfer system. The electron transfer system is composed of a series of enzyme complexes in the inner mitochondrial membrane that oxidise a range of metabolites, including NADH derived from the TCA cycle 5 , fatty acids via beta-oxidation 6 , succinate 7 , proline 8 , and glycerol-3-phosphate in mammals 9 . Electrons derived from these species are funnelled into the Q-junction (co-enzyme Q), before the sequential movement through complex III, cytochrome c and finally respiratory complex IV, where they reduce molecular oxygen in a system that has been well-reviewed 10 .…”
Section: Introductionmentioning
confidence: 99%